Occupational Health Risk Management Measures for Personnel Handling Non-Human Primate Laboratory Animals: An Overview - LI Qian; CHEN Jiaqi; LI Lihong; ZHANG Feiyan; MAO Huaming; LÜ Longbao (Shiyan dongwu yu bijiao yixue)
Owing to their high genetic and physiological similarities to humans, non-human primates (NHPs) have become pivotal animal models in life sciences research and biomedical development. NHP laboratory animals are not only an ideal platform for exploring the mechanisms of neurological diseases and infectious diseases, but they are also widely used in preclinical safety evaluations of macromolecular drugs, which are considered the "gold standard". Nevertheless, this biological similarity increases the risk of zoonotic disease transmission to personnel working with NHP laboratory animals, their tissues, and body fluids. In light of recent domestic and international outbreaks of zoonotic diseases as well as the implementation of the Biosafety Law, this study examines the occupational risk factors encountered by personnel working with NHPs. This includes biological, chemical, and physical factors. This paper also covers common zoonoses, classification of the corresponding pathogens, transmission routes, risk severity levels, and protocols for post-exposure management. A multidimensional prevention and control framework is proposed, which includes the following components. (1) Risk Assessment and Emergency Response: Regularly identify hazards through an Occupational Health and Safety Committee (OHSC) and develop post-exposure emergency protocols. (2) Optimization of Management Systems: Improve facility design, optimize the allocation of personal protective equipment, and enhance health surveillance and vaccination programs. (3) Technical Training and Standardized Operations: Provide specialized training in NHP laboratory animal ethology and biosafety practices. Additionally, implement intelligent monitoring technologies to reduce the occurrence of aggressive incidents. This paper outlines measures designed to enhance health and safety awareness among personnel working with NHP laboratory animals. It emphasizes the need for strengthened guidance on the use of personal protective equipment (PPE) and the standardization of professional operational practices. The goal is to safeguard personnel health and safety, reduce occupational exposure rates, and effectively prevent occupational diseases related to laboratory animals.